The Influence of Security, Privacy, and Trust on the Interest in Using Cash on Delivery Payment Method for Online Purchases of Facial Cleansing Products in Jakarta - Sauki, Mohammad Irfan; Lahindah, Laura (Journal of Business Management Education (JBME), 2024)
The rapid advancement of technology has driven the growth of e-commerce businesses in Indonesia. This growth needs to be accompanied by improvements in customer service, one of which is offering a Cash on Delivery (COD) service. On e-commerce platforms, among the many products that can be transacted using COD are facial cleansing products. This study aims to determine the influence of security, privacy, and trust variables on the interest in using the COD payment method for facial cleansing products in Jakarta. The study employs a quantitative-associative method by distributing questionnaires to 124 respondents who have never used COD. The research uses the SEM-PLS method, conducting outer model tests such as validity and reliability and inner model tests. This study's results show a significant partial influence of security, privacy, and trust variables on customer interest in using the cash-on-delivery payment method. This research is expected to benefit business practitioners by focusing on the importance of shaping perceptions of security, privacy, and trust to encourage customers to use the COD payment method.